Respuesta :
Answer:
y-(-1)=2/3 (x-(-6)
Step-by-step explanation:
So, we want to write an equation that is parallel to the original, and passes thru (-6,-1)... all that needs to be done is plug it in. Using the unsimplified slope intercept form, y-y1=m(x-x1), you will plug in the X and the Y. It will look like
y-(-1)=m (x-(-6), then since we want it to be parallel, you take the same slope from the other equation, because parallel lines never intersect. So then replace the "m" with "2/3". It should look like y-(-1)=2/3 (x-(-6).